PERENCANAAN STRATEGIS SISTEM INFORMASI PENGELOLAAN GURU DI SD NEGERI KUALA BUBON - Suhelmi Suhelmi; Rita Rahniar; Yusnaidi Yusnaidi; Lisa Yani; Iis Marsithah; Sri Milfayetty (JGK (Jurnal Guru Kita), 2022)
Abstract: Strategic Planning of Teacher Management Information System at Sd Negeri Kuala Bubon. The success of schools in the application of IS/IT in an organization or institution depends on the provision of data or information in accordance with the needs of the organization/institution. If it is not managed with careful planning, it is impossible to realize excellent service, so it is necessary to do strategic planning of information systems to support the process of organizational existence so that organizational goals can be achieved. This plan will refer to the Ward and Peppard framework, namely analyzing internal and external businesses, and analyzing IS/IT portfolios. For business analysis use Value Chain and PEST, while for portfolio analysis uses Mc Farlan's portfolio. The results of the analysis are in the form of business processes, data and information needs, and IS/IT portfolios for the current and future management of teachers at SDN Kuala Bubon.